Representation, Experience, and Metaphysics Towards an Integrated Anti-Representationalist Philosophy - Knowles, Jonathan (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book provides an original perspective on the debate about anti-representationalism and the nature of philosophy. This debate has come to prominence in recent years through the work of people like Richard Rorty, Paul Horwich, Huw Price and Amie Thomasson. It is the first book to explicitly consider this well-known pragmatist kind of anti-representationalism in relation to anti-representationalist views in other areas of philosophy, in particular the philosophy of perception and cognitive science. Taking as its point of departure the neo-pragmatism of Rorty and Price, it critiques the way these (and other) thinkers develop, on this basis, a positive view of philosophy and its remit. By examining the debate about representationalism versus anti-representationalism in perception and cognitive science it provides a different way of understanding the significance of neo-pragmatism, as well as providing an independently interesting perspective on these other debates. A central idea in this perspective involves distinguishing between a world-for-us and a world-in-itself, though in a different way from Kant and many other philosophers. The book extends these reflections to examine questions about realism and the limits of metaphysics for anti-representationalist pragmatism, arguing the view can uphold a common sense kind of realism, as well as the value of distinctively philosophical enquiry in metaphysics.
1. Introduction -- 2. Global Expressivism -- 3. Representationalism versus anti-representationalism about perceptual experience and in cognitive science -- 4. The world for us and the world in itself -- 5. Brains in vats -- 6. Anti-representationalism, realism, and anti-realism -- 7. Metaphysics for anti-representationalists? -- References.
Keywords: Language and languages -- Philosophy; Metaphysics; Philosophy of mind; Philosophy of Language; Metaphysics; Philosophy of Mind